An Integrative Method For Enhancing the Ecological Realism of Aquatic Artificial Habitat Designs Using 3D Scanning, Printing, Moulding and Casting - Garg, Aneri; Green, Stephanie J. (Frontiers in Built Environment, 2022)
Identifying features of biogenic (i.e. living) habitat that attract and retain organisms is a key pursuit in ecological habitat selection research. Here we present an integrative method for creating aquatic artificial habitat modules that allow the user to isolate and flexibly manipulate structural and compositional features of replicated biogenic habitats for a range of habitat selection study designs in aquatic environments: This method combines techniques from engineering (3D scanning and printing), paleontology, and visual art (molding and casting) into a stream-lined work flow that is likely to perform on par with or better than other techniques widely used to create artificial replicas of biogenic habitats in terms of design accessibility (availability and cost of construction materials and equipment, and training requirements), scalability (durability, ease of deployment, and reproducibility), and the ecology of the artificial habitat module (degree to which structural and compositional features of the habitat elicit appropriate visual, chemosensory, and auditory cues, and impact of the structure on the surrounding environment). This method can be flexibly modified to answer a variety of questions regarding habitat selection cues, for a range of aquatic biogenic habitat types, and can be adapted for theoretical and applied contexts including cue studies and restoration planning.